Facile Synthesis of Substituted 4-Alkoxy-2-oxazolines and Exploration of the Reaction Mechanism - Zhu, Jianming; Li, Xiaolong; Wang, Guimin; Li, Bo; Xu, Zhijian; Tian, Shikai; Hall, Adrian; Shen, Jingshan; Shi, Jiye; Zhu, Weiliang (Synthesis, 2016)
Substituted 4-alkoxy-2-oxazolines have been synthesized via the reaction of nitriles with beta-hydroxyacetals promoted by trifluoromethanesulfonic acid. The reaction is proposed to be initiated by the protonation of the acetals to produce carbocations that are then attacked by nitrogen atom of the nitriles, followed by an intramolecular cyclization reaction to form the 4-alkoxy-2-oxazolines. The proposed reaction mechanism has been validated by quantum chemistry calculations, key intermediate synthesis, and NMR spectra.
Keywords: 4-alkoxy-2-oxazoline; benzonitrile; β-hydroxyacetal; trifluoromethanesulfonic acid; reaction mechanism; quantum chemistry calculation